The subsurface thermal state of Svalbard and implications for geothermal potential. (June 2023) - Senger, Kim; Nuus, Matthijs; Balling, Niels; Betlem, Peter; Birchall, Tom; Christiansen, Hanne H.; Elvebakk, Harald; Fuchs, Sven; Jochmann, Malte; Klitzke, Peter; Midttømme, Kirsti; Olaussen, Snorre; et al.
Highlights: Geothermal gradients of 24–55 °C/km are reported from 14 deep petroleum and research boreholes onshore svalbard. Strong lateral variation in heat flow exists onshore svalbard. 232 new thermal conductivity values are reported from drill cores in cenozoic and mesozoic strata. Thermal conductivity is largely lithology controlled, with sandstones (3.92 W/m K) exhibiting higher thermal conductivity than shales (2.31 W/m K). Data and knowledge gaps are identified, largely related to analyses on strata older than middle triassic and geological controlling factors for the spatial variability in heat flow. Abstract: Svalbard is a High Arctic Archipelago at 74–81°N and 15–35 °E under the sovereignty of Norway. All settlements in Svalbard, including the capital of Longyearbyen (population 2400), currently have isolated energy systems with coal or diesel as the main energy source. Geothermal energy is considered as a possible alternative for electricity production, as a heat source in district heating systems or harnessed for heating and cooling using geothermal heat pump installations. In this contribution we present the until now fragmented data sets relevant to characterize and assess the geothermal potential of Svalbard. Data sets include petroleum and deep research boreholes drilled onshore Svalbard, 14 of which have recorded subsurface temperature data at depths below 200 m. Geothermal gradients on Spitsbergen vary from 24 °C/km in the west to 55 °C/km in the south-east, with an average of 33 °C/km. Four deep research boreholes were fully cored and analyzed for thermal conductivity. These analyses were complemented by thermal conductivity calculated from wireline logs in selected boreholes and four measurements on outcrop samples. 1D heat flow modelling on five boreholes calibrated with the measured thermal conductivities offers insights into heat transfer through the heterogeneous sedimentary succession. Offshore petroleum boreholes in the south-western Barents Sea and marine heat flow stations around Svalbard provide a regional framework for discussing spatial variation in heat flow onshore Svalbard, with emphasis on the effects of erosion and deposition on the thermal regime. We conclude that Svalbard's geology is well suited for geothermal exploration and potential production, though challenges related to permafrost, the presence of natural gas, heterogeneous reservoir quality and strongly lateral varying heat flow need to be adequately addressed prior to geothermal energy production. Specifically for Longyearbyen, high geothermal gradients of 40–43 °C/km in the nearest borehole (DH4) suggest promising sub-surface thermal conditions for further exploration of deep geothermal potential near the settlement.